Evaluation of Relationship between Neutrophil to Lymphocyte Ratio and Rheumatoid Arthritis Severity - Shazia Anwar, Adil Khan, Muhammad Ammar Khan, Zafar Abdul Nabi, Salman Khan, Shafi Muhammad Wassan, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Persistent inflammation and progressive joint damage characterize autoimmune arthritis (RA), a long-term inflammatory condition Objective: To assess the association between the neutrophil-lymphocyte index and the severity of autoimmune arthritis, evaluating its potential as a marker of disease activity Study Design: Cross-sectional observational study. Study Setting: The study was conducted at Fatima Memorial Hospital, Lahore over 6 months duration. Methodology: This study included 140 RA patients, all fulfilling the 2010 ACR/EULAR classification criteria. Data on demographics, clinical features, and laboratory results, such as CBC, were recorded. NLR was calculated, and the DAS28 score was used to determine disease severity. Results: The mean neutrophil to lymphocyte ratio (NLR) among all RA patients was 3.21 ± 1.85, with a significant increase across disease activity groups: 2.14 ± 1.02 in remission, 2.78 ± 1.23 in low, 3.42 ± 1.72 in moderate, and 4.51 ± 1.98 in high disease activity (p < 0.01). NLR was positively correlated with RA severity (r = 0.32, p < 0.01). Additionally, ESR and CRP levels were significantly elevated in patients with higher disease activity, further supporting the relationship between NLR and systemic inflammation. Conclusion: NLR was found to be a significant biomarker for assessing RA severity. Its simplicity and accessibility make it a useful tool for clinical monitoring subjects diagnosed with RA, though further studies are required to validate its predictive value. Keywords: Biomarker, Inflammation, Neutrophil to Lymphocyte Ratio, Severity, Rheumatoid Arthritis.